Molecular detection of GSTM and GSTT genes with biomarkers studies in samples of Iraqi breast cancer patients - Alhayali, Hasan; Hojati, Zohreh (International Journal of Innovative Research and Scientific Studies, 2025)
To identify genes like GSTT and GSTM’s impact on breast cancer development, as well as their relationship with age, blood group, white blood cell count, erythrocyte sedimentation rate, and lipoprotein levels. Genomic DNA was extracted from blood samples of 75 breast cancer cases and 40 control subjects, and detection was performed using multiplex PCR-based methods and biomarker examination. Gel electrophoresis showed significant differences in nucleic acid bands from GSTT and GSTM genes in patients with breast cancer. The Type O blood group was more prevalent, with a significantly higher age (51.74 ±1.56) compared to the control groups (34.50 ±3.03). White blood cell count was also significantly higher in the breast cancer group. The study revealed significant differences in erythrocyte sedimentation rate, high-density lipoprotein, and low-density lipoprotein levels in breast cancer patients compared to control groups, with both groups showing higher levels of these markers. The study indicates that GSTT and GSTM may increase breast cancer susceptibility, with the Type O blood group being more prevalent in patients. Other factors, such as white blood cell count, erythrocyte sedimentation rate, high-density lipoprotein, low-density lipoprotein, immunoglobulin G, and blood sugar, were also significantly higher in patients with breast cancer.